PE-4-ME : teaching lifelong health and fitness - Summerford, Cathie, 1957- (Champaign, IL : Human Kinetics, 2000)
Describes a year-long plan for a kindergarten through high school program that combines physical activity with movement concepts, social skills, stress reduction, nutrition, school safety, and drug resistance education; featuring 138 games, reproducible handouts, and advice on creating a captivating class environment.
"A brain-compatible, thematic approach"--Cover.
Includes bibliographical references (p. 254).
Professional
Keywords: Health education (Middle school) -- United States; Health education